Supporting adolescents with autism in secondary schools - Odom, Samuel L. (The Guilford Press, 2023)
"The book discusses the Center on Secondary Education for Students with Autism (CSESA), which is designed to support all students with autism in high school, and the breadth of the learning needs for those autistic students is broad. For many of these students, four domains of emphasis are important: Transition and Families, Academics, Peer and Social Competence, and Personal Independence and Behavior. The CSESA program consists of specific component interventions and practices that address each of these domains, which are highlighted in the book chapters"--